Analisis Penerapan Pembelajaran Proyek Berbasis STEAM untuk Meningkatkan Kreativitas Anak Usia Dini di TK Negeri Model Mataram - Maulida Sulastri; Gunawan Gunawan; Ika Rachmayani; Ni Luh Putu Nina Sriwarthini (Indonesian Journal of Elementary and Childhood Education, 2025)
This research aimed to implement STEAM-based project learning and measure its effect on the creativity of Group B1 children at the Mataram Model State Kindergarten. This Classroom Action Research (CAR) employed the Kemmis and McTaggart model, conducted in two cycles, with each cycle consisting of two meetings. The research procedures included planning, action implementation, observation, and reflection. The subjects of this study were all 8 children (5 boys and 3 girls) from Group B1 at the Mataram Model State Kindergarten. Data analysis was performed using descriptive qualitative techniques. The research findings indicated a significant increase in children's creativity after the implementation of STEAM-based project learning. The implementation of STEAM-based project learning achieved a 53.3% success rate in Cycle I, which further increased to 86.6% in Cycle II. Concurrently, children's creativity levels rose from 37.5% in the pre-cycle to 62.5% in Cycle I, and ultimately to 87.5% in Cycle II. The intervention was deemed successful as it met the achievement level indicator of 76.0%. Therefore, it can be concluded that the application of STEAM-based project learning effectively enhances the creativity of children in Group B1 at the Mataram Model State Kindergarten.